Reduced Blood Glucose Levels in Diabetic Patients After Using a Combination of Progressive Muscle Relaxation (Pro-Mure) and Slow Deep Breathing Exercises (SD-Bex) - Nabila, Shanaz Leka; Sukartini, Tintin; Khamida, Khamida (Poltekkes Kemenkes Surakarta, 2024)
Background: One of the causes of diabetes mellitus is a person's lifestyle, namely their level of physical inactivity. So, to avoid complications, persons with diabetes mellitus require both pharmaceutical and non-pharmacological treatments to lower blood glucose values. Finding out if people with diabetes mellitus might reduce their blood glucose levels by combining a technique that involved slow deep breathing and progressive muscular relaxation was the primary goal of the research. Methods: This study is quasi-experimental because it uses a control group design with pre- and post-tests. The number of respondents is 34, and the method of sampling is purposive sampling. Twenty to twenty-five minutes of a combination of progressive muscle relaxation (Pro-Mure) and slow deep breathing exercises (SD-Bex) were administered to the experimental group, while the control group received the usual course of intervention. Values of blood glucose levels were the dependent variable. With a p-value of less than 0.05, the study used the Wilcoxon Signed Rank Test to compare outcomes before and after treatment and the Mann-Whitney test to compare the experimental group to the control group. Results: We found that the intervention group's blood glucose value was 0.001 and the control group's was 0.025. A p-value of 0.001 was found on the value of blood glucose levels between the experimental group and the control group as a result of the study utilising the Mann-Whitney test. Conclusion: Those suffering from diabetes mellitus can find relief from their symptoms by combining the techniques of Progressive Muscle Relaxation with Slow Deep Breathing. Additionally, the method is simple to apply.